William Congreve - Dobrée, Bonamy (Writers and Their Work Series., 1967)
'What plays! What wit!' Byron's tribute to Congreve was a fitting one: the consummate mastery of language, wonderfully absurd comic characters, and especially the exquisite wit and gaiety of the lovers' exchanges, mark his plays as some of the greatest comedies in the English language. But if Congreve represents the flowering of Restoration comedy, he also stands apart from his fellow playwrights; contrasted with Etherege's amorality and Wycherley's wit, his.